Enhancing Science Learning: The Role of Educational Games in Elementary Classrooms - Sari, Ida Puspita; Rohmani (Indonesian Journal of Educational Research and Review, 2024)
The low learning outcomes of science in elementary schools is a challenge that requires an innovative approach in the learning process. The use of educational games as interactive learning media is believed to be able to increase students' interest and understanding of science lessons in elementary school. This study aims to analyze the effectiveness of using educational game media in improving science learning outcomes in elementary schools. The method used in this research is Systematic Literature Review. Researchers collected journal articles from Google Scholar, Research Gate, SINTA, and Web of Science in the time span from 2019 to 2023. The data analysis technique used is quantitative descriptive obtained from 10 review articles that are in accordance with the research study. The results of the analysis show that educational games have interactive properties that can attract students' attention, thus increasing their engagement and motivation during the teaching and learning process. In addition, this study also identified various types of educational game media that have been applied in science learning, as well as factors that influence the effectiveness of their use. The findings are expected to provides knowledge for teachers and curriculum developers to design innovative and effective learning strategies in improving student learning outcomes in science learning in elementary schools.